2016
DOI: 10.1039/c5fd00154d
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive chemically specific measurement of subsurface temperature in biological tissues using surface-enhanced spatially offset Raman spectroscopy

Abstract: Here we demonstrate for the first time the viability of characterising non-invasively the subsurface temperature of SERS nanoparticles embedded within biological tissues using spatially offset Raman spectroscopy (SORS). The proposed analytical method (T-SESORS) is applicable in general to diffusely scattering (turbid) media and features high sensitivity and high chemical selectivity. The method relies on monitoring the Stokes and anti-Stokes bands of SERS nanoparticles in depth using SORS. The approach has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…So far applications for brain measurements through the skull have been proposed (see Figure 31) [411], as well as blood glucose monitoring [412] and Stokes/anti-Stokes temperature sensing of tissue [413,414].…”
Section: Applicationsmentioning
confidence: 99%
“…So far applications for brain measurements through the skull have been proposed (see Figure 31) [411], as well as blood glucose monitoring [412] and Stokes/anti-Stokes temperature sensing of tissue [413,414].…”
Section: Applicationsmentioning
confidence: 99%
“…Very recently, Gardner et al demonstrated that apart from monitoring chemical properties of samples SORS and SESORS could be used to monitor their physical properties too, such as temperature [53,54]. The basic approach relies on monitoring the ratio of corresponding Stokes and anti-Stokes Raman bands.…”
Section: Monitoring Of Sample Physical Propertiesmentioning
confidence: 99%
“…The field of nanomaterials for photonics applications is rapidly expanding, with increasingly sophisticated materials being developed to monitor a plethora of physical and chemical properties, including but not limited to temperature, 1,2 pH, 3,4 redox, 3 glucose, 5 DNA 6 and proteins such as neurotransmitters, 7 with many of these being complex in vivo targets. One such active area is the development of advanced nanomaterials as therapeutics for the next generation of photothermal therapies for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Potential nanomaterial mediated hyperthermia treatments require the temperature not only to be elevated, but also accurately monitored and maintained within relatively narrow therapeutic thermal windows (41-48°C) for effective and selective treatments. 9 However, until very recently non-invasive temperature sensing of tissue at depth was not possible 1,2,8,18 representing one of the main barriers to the introduction of photo thermal therapies (PTT). 9 Classically, Raman spectroscopy is seen as a technique limited to the sample surface in diffusely scattering samples such as biological tissues, with the sampling depth often limited to a few hundreds of micrometres.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation